Home Environment, Bilingual Preschooler’s Receptive Mother Tongue Language Outcomes, and Social-Emotional and Behavioral Skills: One Stone for Two Birds? - Sun, He (Frontiers in Psychology, 2019)
The current study seeks to illustrate the impact of child bilinguals’ mother tongue language (MTL) exposure and reading activities at home on the children’s mother tongue language (MTL) proficiency and their socio-emotional and behavioral skills (SEBS). Data from 202 Singapore preschoolers (4 to 5 years old) who are learning English and Mandarin were analyzed. A parental questionnaire and standard Mandarin tests (i.e., receptive vocabulary, receptive grammar, and verbal fluency) were used to assess children’s Mandarin language-literacy environment at home, as well as their Mandarin proficiency. Children’s SEBS were evaluated with the Strengths and Difficulties Questionnaire (parental version). A series of variables which might influence SEBS and MTL proficiency (e.g., gender and SES) were controlled and SEMs were used to conduct data analysis. Results demonstrated that both Mandarin language and literacy environmental factors are related to children’s Mandarin outcomes, while only literacy environmental factors affect children’s difficulty level and prosocial skills. This suggests that good parental support in bilingual children’s MTL literacy should be promoted not only for the sake of their early language development but also because of the potential benefits to their social emotional wellbeing.